La comunidad orquideológica en la Reserva de la Biosfera Sierra del Rosario, Cuba - Alfredo García-González; Rolando Pérez Márquez (Revista de Biología Tropical, 2011)
Teniendo en cuenta la escasez de estudios previos que permitan apreciar el efecto de la antropización sobre las comunidades de orquídeas en la Reserva de la Biosfera Sierra del Rosario, al occidente de Cuba; se procedió a realizar un estudio comparativo entre un hábitat conservado (El Salón; ES) y uno antropizado (El Taburete; ET) y se encontraron en total 27 especies de forófitos, 20 especies presentes en ET (98 forófitos) y 16 especies en ES (76 forófitos). Por lo tanto se identificaron 22 géneros de orquídeas, 26 especies y 8 326 plantas. En ES fueron 15 géneros, 18 especies y 3 251 plantas, en ET, 17 géneros, 18 especies y 5 075 plantas. Oeceoclades maculata, una especie invasora, fue la más abundante. Ambas localidades tienen una similaridad de especies de 57.14%. Las especies más dominantes fueron: Microchilus plantagineus en ES y O. maculata en ET. La dominancia en ES es de 69.27% y en ET de 81.79%. Es importante elaborar planes de manejo enfocados a controlar O. maculata en ambas áreas, y en restablecer el estrato arbóreo original de la zona antropizada. The orchid community in the Biosphere Reserve Sierra del Rosario, Cuba. The Biosphere Reserve Sierra del Rosario is located in Western Cuba and two different areas can be characterized: one for tourism and forestry activities, El Taburete (ET), and the other for conservation and research, El Salón (ES). With the aim to know the effect of visitation activities on the orchid community in the Reserve, a comparative study between the disturbed area and the preserved one was undertaken. The field work, held between 2004-2005, consisted on four transects in each locality (10x100m, 0.1ha). For each transect, the existing orchid species (terrestrial and epiphytic), kind of phorophytes, and level of occupation were identified. Different analysis were considered: dominance-diversity, Sorensen similarity, the dominance index and the relative abundance of the most abundant species. Our results showed 27 phorophytes species, 20 species in ET (98 phorophytes), and 16 species in ES (76 phorophytes). A total of 22 genus, 26 species and 8 326 individuals of orchids were identified. In ET, 17 genus, 18 species and 5 075 individuals were found, while for ES were 15 genus, 18 species and 3 251 individuals. Both locations have a similarity of species of 57.14%. Oeceoclades maculata, an invasive species, was the most abundant. The most dominant species were Microchilus plantagineus in ES and O. maculata in ET. The dominance in ET was of 81.79%, while in ES of 69.27%. It is important to sketch management plans focused on controlling O. maculata in both areas, and the restoration of the disturbed area. Rev. Biol. Trop. 59 (4): 1805-1812. Epub 2011 December 01.